A new species of the genus Gracixalus (Amphibia: Anura: Rhacophoridae) from Southern Guangxi, China - Mo, Yunming; Zhang, Wei; Luo, Yu; Zhou, Shichu; Chen, Weicai (Zootaxa, 2013)
A new species of the genus Gracixalus is described from Nonggang National Nature Reserve, based on eleven specimens from evergreen karst forests in Sino-Vietnamese border region of southern China. The new species, Gracixalus nonggan-gensis sp. nov., is medium sized species of Gracixalus that can be distinguished from its congeners by a combination of the following characters: SVL ranging from 29.9–35.3 mm in males and 33.6–38.0 mm in females; vomerine teeth absent; distinct tympanum as wide as the disc of finger III; the lower part of the tympanum with many small tubercles; tibiotarsal articulation reaching the tip of the snout; dorsum smooth yellowish-olive in life with a wide, dark-green irregular mark; throat, chest and belly white with light grey-blue tint and brown marbling; broad, dark olive, transverse stripes on limbs; finger webbing absent, toes one-third webbed; male with internal subgular vocal sac. Based on a 16S ribosomal RNA mi-tochondrial gene fragment, G. nonggangensis sp. nov. forms a monophyletic group embedded within the genus Gracixalus.